What I am doing wrong here?

Also does it matter that there are only two variables in the third line? All the examples I have looked at for solving three equations with three variables had three variables in each line.

2x + y + z = 21

2y + x + z = 20

2x + 2y = 22

define x

x + y = 11

x = y -11

substitute into line 1 and 2:

2(11 - y) + y + z = 21

22 - 2y + y + z = 21

22 + z = 21 + y

z = y - 1

2y + (y-11) + z = 20

3y - 11 + z = 20

3y + z = 31

substitute again:

3y + (y-1) = 31

4y = 32

y = 8

thanks!